Japan’s legal culture trap and the dilemma of South Korean pursuit of transitional justice - Chukwuma, Nzube A. (Contemporary justice review, 2025)
At the end of World War II, countries involved in war crimes issued apologies for their large-scale atrocities. In East Asia, studies showed that Japan has apologized for war crimes committed against South Korean comfort women at the comfort station. Yet, since 1991, the persistent court cases against Japan suggest Japan’s wartime apologies have failed to reconcile wartime survivors and yield intergroup forgiveness. Why is this so? The study interrogates the legal culture of Japan as a measure to unravel South Korea’s intractable unacceptance of Japan’s war apology claims. We explored culture as a peculiar group identity and focused on the distinctive Japanese legal culture associated with Nihonjinron. Findings revealed that Japan’s legal culture of giri is endogenous in contrast to South Korea’s exogenous transitional justice of litigation culture, frequently used by survivors to pursue justice. These dualities of legal culture between Japan and South Korea, notably Japan’s intricacies of interpersonal apology, shame culture, and apology mannerisms, have political, economic, and security ramifications between Japan and South Korea. The study suggests the establishment of the Truth Commission as an alternative middle ground for a dispute resolution mechanism between Japan and its neighbours.